2010
DOI: 10.1177/0734242x10361506
|View full text |Cite
|
Sign up to set email alerts
|

Household waste prevention — a review of evidence

Abstract: This paper reports a synthesis of policy-relevant evidence on household waste prevention, based on a UK portfolio of primary research and a broad international review. Waste prevention was defined as strict avoidance, reduction at source (e.g. home composting) and reuse (for the product's original purpose) - recycling was excluded. A major focus was on consumers. Waste prevention is not one but many behaviours; the review revealed a general hierarchy in their popularity, from donating goods to charity at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 16 publications
4
85
0
4
Order By: Relevance
“…If households understand that food waste leads to increase cost of waste management, water shortage, energy and impact food security, this knowledge will compel them to change behaviour on their consumption lifestyle. According to Cox et al (2010) creating awareness among households and making them to understand the food waste impacts on the environment is an effective component for behaviour change towards sustainable food waste disposal. Furthermore, enhancing knowledge on environmental education on households could start from preschool children, inculcating in them to understand their responsibilities as environmental stakeholder and making them to know they have responsibilities and roles to play to reduce wastage in their consumption behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…If households understand that food waste leads to increase cost of waste management, water shortage, energy and impact food security, this knowledge will compel them to change behaviour on their consumption lifestyle. According to Cox et al (2010) creating awareness among households and making them to understand the food waste impacts on the environment is an effective component for behaviour change towards sustainable food waste disposal. Furthermore, enhancing knowledge on environmental education on households could start from preschool children, inculcating in them to understand their responsibilities as environmental stakeholder and making them to know they have responsibilities and roles to play to reduce wastage in their consumption behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of 'joined-up' research, such as that sponsored by Defra on household waste behaviour (Brook Lyndhurst, SMP and RRF, 2009;Cox et al, 2010;Tucker and Douglas, 2007), means that the evidence base lacks coherence: motivations for, and barriers to, business waste prevention are therefore not fully understood. No studies were found that had used a systematic or theory-based approach to examine the behavioural drivers of waste prevention in business, including the relative importance of different drivers.…”
Section: Motivations and Barriersmentioning
confidence: 99%
“…This article results from a major research project commissioned by the Department for Environment, Food and Rural Affairs (Defra) in England, which aimed to map and collate the available evidence on business waste prevention in order to help inform future policy development (Wilson et al, 2007). This complements earlier work on household waste prevention (Brook Lyndhurst, SMP and RRF, 2009;Cox et al, 2010). Taken together, the two reviews cover all aspects of both business and household waste prevention.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is widespread throughout the waste field, and poor quality or unavailable data prohibits accurate system analyses and comparisons between programs [29]. Data on waste prevention are especially scarce and/or poor [48]. A major component of the waste management framework is the establishment of methods for the collection of sufficient data on a regular basis and analyzing well-defined performance indicators.…”
Section: Lack Of Datamentioning
confidence: 99%